Biofilms as potential reservoirs of stony coral tissue loss disease - Evans, James S.; Paul, Valerie J.; Kellogg, Christina A. (Frontiers in Marine Science, 2022)
Since 2014, corals throughout Florida’s Coral Reef have been plagued by an epizootic of unknown etiology, colloquially termed stony coral tissue loss disease (SCTLD). Although in Florida the movement of this waterborne coral disease has been consistent with natural transport via water currents, outbreaks in the Caribbean have been more sporadic, with infections occurring in locations inconsistent with spread via natural means. Often Caribbean outbreaks have been clustered near ports, potentially implicating ships as mediators of SCTLD into new regions. Biofilms attached to ship hulls, ballast tank walls, or other surfaces could represent a possible vector for the disease. We investigated whether bacteria shed by healthy and SCTLD-diseased corals would form distinct biofilms, and whether a SCTLD signal would be detectable within biofilm bacterial communities. Stainless steel plates serving as proxies for ship hulls, ballast tank walls, and other colonizable surfaces were incubated for three days in filtered seawater mesocosms containing healthy or SCTLD-infected corals. Resulting biofilm bacterial communities were characterized through sequencing of the V4 region of the 16S rRNA gene. We determined that bacteria shed by healthy and diseased corals formed significantly different biofilms consisting of highly diverse taxa. Comparison with 16S data from previous SCTLD investigations spanning different coral species, collection locations, years, and source material revealed the presence of numerous genetically identical sequences within the biofilm bacterial communities formed during exposure to SCTLD-infected corals, including several previously identified as possible SCTLD bioindicators. These results suggest ship-associated biofilms may have the potential to be vectors for the transmission of SCTLD into new regions.